Design and Implementation of a Detection System for pH Levels, Moisture Content, and Sweetness in Honey - M Suhairi; Suhaila Suhaila; Nurraudya Tuz Zahra; Hazimah Widyagustin (Politeknik Negeri Padang, 2026)
This research aims to design and build a honey detection device. The device is designed to detect three important parameters in honey such as pH, water content, and color. A pH sensor is used to measure the acidity level of honey, which is an important indicator in determining the freshness and quality of honey. A Soil Moisture sensor is adapted to measure the water content in honey, as the appropriate moisture level significantly affects the stability and quality of honey. Meanwhile, an LDR sensor is used to detect the color of honey, which often serves as a visual indicator of the quality and type of honey. Data collected from these three sensors is processed by an ESP32 and displayed in Liquid Crystal Display (LCD) with easily understandable format, enabling users to assess honey quality quickly and accurately. Test results show that this device can provide consistent and reliable data, making it a potential solution for honey quality evaluation in the field. This research also utilizes push buttons for displaying data and resetting or reconfiguring the system. Based on the testing conducted, Uray Honey has the highest water content (11.90%) and the lowest acidity level (4.67). Real Honey with water content (8.19%) and pH (3.43), and TJ Honey with water content (8.68%) and pH (3.41) have similar profiles in terms of water content and pH; however, Real Honey is darker in color (11.05) compared to Uray Honey (9.97). Super Honey has consistent color and water content (8.11%) but has a lower color value (9.59) compared to other honeys and has a pH of (3.41).